First Report on CRISPR/Cas9-Based Genome Editing in the Destructive Invasive Pest Tuta Absoluta (Meyrick) (Lepidoptera: Gelechiidae) - Ji, Shun-Xia; Bi, Si-Yan; Wang, Xiao-Di; Wu, Qiang; Tang, Yan-Hong; Zhang, Gui-Fen; Wan, Fang-Hao; Lü, Zhi-Chuang; Liu, Wan-Xue (Frontiers in Genetics, 2022)
The tomato leaf miner Tuta absoluta (Meyrick) is one of the world’s most destructive pests of tomato, and because of its severe economic impacts, as well as the development of pesticide resistance, the species has been intensively studied, especially in regard to the identification of targets for T. absoluta control. However, functional genomic studies of T. absoluta have been constrained by a lack of effective genetic tools. Therefore, the aim of the present study was to develop a CRISPR/Cas9 zygote microinjection protocol for generating heritable mutations in T. absoluta, using the ommochrome synthesis gene cinnabar as an easily evaluated target gene. The injection of fertilised eggs with Cas9 protein and four sgRNAs, which targeted cinnabar exon 3, resulted in a mutagenesis rate of 31.9% for eggs reaching adulthood, and cinnabar mutagenesis resulted in either red or mosaic eye colour phenotypes. As such, this study is the first to report a complete and detailed CRISPR/Cas9 workflow for the efficient genome editing of the globally important invasive pest T. absoluta. The application of this robust genome-editing tool to T. absoluta will greatly facilitate the discovery of suitable RNAi control targets and the subsequent development of novel control strategies.